Workplace Education Programs in Small- and Medium-Sized Michigan Firms - Kevin Hollenbeck (W.E. Upjohn Institute for Employment Research, 1992)
This paper presents a systematic, baseline picture of workplace education programs in small and medium-sized businesses (less than 500 employees) in Michigan. Specifically, it addresses why some firms are offering and other firms are not offering workplace education programs, what are the characteristics of the programs being provided, and what are the impacts of these programs on firms and employees. The paper draws upon two data sources. Case studies of 28 Michigan businesses were undertaken between May 1991 and July 1992 and a combination mail/telephone survey of small businesses in Michigan was conducted in early 1992. The paper finds that a significant share of the employed population, perhaps 25 to 40 percent of hourly workers, have basic skills difficulties that are reported to impair their productivity. Yet very few of the workers have an opportunity to receive education in basic skills through their workplace.
Keywords: J0; I2; 330; workplace; literacy; programs; education; productivity; Michigan; Hollenbeck